Critical Evaluation on WSNs Positioning Methods (International Journal of Innovative Research in Computer Science & Technology, 2021)
WSN gained a lot of attention because they  are small and economical devices with low power  utilization, and finite computing resources are progressively  being enfolded in various application situations, including  environmental monitoring, reconnaissance tracking, and  health monitoring. In many applications of this type, node  localization is an intrinsic parameter of the system. To  report events origin, routing, and network coverage (A&Q),  assist group querying of the sensors Localization process is  mandatory. Localization is categorized into two types,  which are a range-based or range-free scheme which is  further divided into two sub-schemes as a fully and hybrid.  For the detailed analysis and study, we are going to  investigate localization schemes based on static and mobile  WSN in this work. This research opens the new paradigm  and future planning for the localization algorithms mainly  how sensors are deployed? What kind of measures are taken  into account to boost the algorithms so that the system can  calibrate itself in changing environments?
Keywords: RSSI; localization; anchor nodes; wireless sensor networks; mobile computing